2017
DOI: 10.21873/anticanres.11531
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of BMI-1 But Not MEL-18 Expression in Pulmonary Squamous Cell Carcinoma

Abstract: BMI-1 expression, but not MEL-18, is associated with a favorable prognosis and is a possible prognostic factor of pulmonary squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In addition, several recent studies reported that the upregulation of BMI-1 was associated with poor prognosis in many cancers, including cancer of the renal cell, tongue, uterine, and lung. 17 , 32 , 33 , 34 Therefore, we analyzed the correlations between the salivary BMI-1 levels and clinical outcomes in patients with SACC. Our data showed that patients whose saliva contained high levels of BMI-1 had poor overall and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent studies reported that the upregulation of BMI-1 was associated with poor prognosis in many cancers, including cancer of the renal cell, tongue, uterine, and lung. 17 , 32 , 33 , 34 Therefore, we analyzed the correlations between the salivary BMI-1 levels and clinical outcomes in patients with SACC. Our data showed that patients whose saliva contained high levels of BMI-1 had poor overall and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%